Mitochondria in Sex Hormone-Induced Disorder of Energy Metabolism in Males and Females - Yin, Lijun; Luo, Man; Wang, Ru; Ye, Jianping; Wang, Xiaohui (Frontiers in Endocrinology, 2021)
Androgens have a complex role in the regulation of insulin sensitivity in the pathogenesis of type 2 diabetes. In male subjects, a reduction in androgens increases the risk for insulin resistance, which is improved by androgen injections. However, in female subjects with polycystic ovary syndrome (PCOS), androgen excess becomes a risk factor of insulin resistance. The exact mechanism underlying the complex activities of androgens remains unknown. In this review, a hormone synergy-based view is proposed for understanding this complexity. Mitochondrial overactivation by substrate influx is a mechanism of insulin resistance in obesity. This concept may apply to the androgen-induced insulin resistance in PCOS. Androgens and estrogens both exhibit activities in the induction of mitochondrial oxidative phosphorylation. The two hormones may synergize in mitochondria to induce overproduction of ATP. ATP surplus in the pancreatic β-cells and α-cells causes an excess secretion of insulin and glucagon, respectively, leading to peripheral insulin resistance in the early phase of type 2 diabetes. In the skeletal muscle and liver, the ATP surplus contributes to insulin resistance through suppression of AMPK and activation of mTOR. Consistent ATP surplus leads to mitochondrial dysfunction as consequence of mitophagy inhibition, which provides a potential mechanism for mitochondrial dysfunction in β-cells and brown adipocytes in PCOS. The hormone synergy-based view provides a basis for the over activation and dysfunction of mitochondria in PCOS-associated type 2 diabetes. The molecular mechanism for the synergy is discussed in this review with a focus on transcriptional regulation. This view suggests a unifying mechanism for the distinct metabolic roles of androgens in the control of insulin action in men with hypogonadism and women with PCOS.